2016
DOI: 10.1088/1748-0221/11/02/p02006
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of open-loop plasma vertical movement response in the Damavand tokamak using closed-loop subspace system identification

Abstract: A formulation of a multi-input single-output closed-loop subspace method for system identification is employed for the purpose of obtaining control-relevant model of the vacuumplasma response in the Damavand tokamak. Such a model is particularly well suited for robust controller design. The accuracy of the estimate of the plant dynamics is estimated by different experiments. The method has been described in this paper is a worst-case identification technique, that aims to minimize the error between the identif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Before selection of the method, linearity or nonlinearity of the system behavior must be determined. This subject has been discussed in Darestani Farahani and Abbasi Davani (2016). It is shown that the Damavand tokamak has a nonlinear inherent.…”
Section: Validation Of the Proposed Methods By Using Experimental Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Before selection of the method, linearity or nonlinearity of the system behavior must be determined. This subject has been discussed in Darestani Farahani and Abbasi Davani (2016). It is shown that the Damavand tokamak has a nonlinear inherent.…”
Section: Validation Of the Proposed Methods By Using Experimental Datamentioning
confidence: 99%
“…For a selected operating point, different data shots have been gathered, in a way that the coefficients of the controller and the initial conditions of the system are identical for all of them. In this paper, we use the only available data set, namely, the experimental data that are collected by authors in Darestani Farahani and Abbasi Davani (2016). In order to compare the identification accuracy achieved by the proposed FODNN model and the integer order dynamic neural network, the performance index,…”
Section: Comparison Between the Proposed Methods Based On Fodnn And Inmentioning
confidence: 99%
See 3 more Smart Citations